Association between clinicopathological features of breast cancer with adipocytokine levels and oxidative stress markers before and after chemotherapy. Issue 3 (22nd December 2020) - GRUPIŃSKA, JOANNA; BUDZYŃ, MAGDALENA; BRZEZIŃSKI, JACEK J.; GRYSZCZYŃSKA, BOGNA; KASPRZAK, MAGDALENA P.; KYCLER, WITOLD; LEPOROWSKA, EWA; ISKRA, MARIA
No abstract available